The Effect of COVID-19 on Family Support for Home-Schooling in Urban Areas - Osman S. Ahmed; Asma Ahmed; Mohd E. Eltahir; Salah Gad; Ali S. Ahmed; Zezit M. Noufal; Alaa Zuhir Al Rawashdeh (Ital Publication, 2023)
The objective of the study is to clarify that the family participated in COVID-19 as a home-schooling family. The sample was selected according to the geographical distribution of schools in the eastern region of Khartoum. Data was collected through a questionnaire and interviews. The most important result is that there is an increasing interest from parents to support home-schooling despite the challenges of continuing learning, such as the widening digital divide in technology, previous experience, and poor network connectivity. This research paper focused on the point of view of parents in the city of Khartoum on supporting home-schooling according to social variables related to both mother and father, and the paper concluded that parents of students in private schools are more supportive of home education. Also, most of the parents of students who support home-schooling have reached their university level of education and post-university and belong to the youth age group. Although parents emphasize the importance of home-schooling during the COVID-19 infection, there are challenges associated with providing home-schooling for their children. Doi: 10.28991/ESJ-2023-07-05-021 Full Text: PDF